How adults learn: The meaning of adult education - Jack Mezirow (Adult Education Research Conference, 1993)
The process of critical reflection, rational discourse and reflective action is central to significant adult learning. This process implies criteria for planning emancipatory adult learning and education and for envisioning a learning society.